What level of competence in emergency skills do registrars in various specialities possess? - Dufourq, Nicholas (My University, 2014)
To determine the level of self-assessed competence various registrars possessed in emergency skills as well as to identify any factors that may have contributed to their level of competence. Materials and Methods: Questionnaires were completed by registrars working in General Surgery, Internal Medicine, Psychiatry and Radiology in three academic hospitals in Johannesburg. Information regarding demographic data, educational background, work experience in emergency-related environments and resuscitation courses attended were collected. Registrars rated their level of perceived competence in a list of 25 emergency skills according to a ranking scale of 1 to 5. Results: A total number of 94 registrars participated in the study which amounted to an estimated response rate of 35%. General Surgery registrars had the highest mean competence scores of 3.7 and 3.9 for the respective basic and advanced skills groups. General Surgery and Internal Medicine registrars had the highest mean competence scores of 3.7 for the intermediate skills group. Psychiatry registrars had the lowest mean competence scores of 2.7, 2.4 and 1.5 in each of the skill groups. Registrars who had current certification in a PALS course had competence scores 0.6 units higher than others in both basic (p=0.027) and advanced (p=0.035) emergency skills. Conclusions: General Surgery and Internal Medicine registrars have a higher level of perceived competence in various emergency skills. The General Surgery group rated themselves the highest in levels of competence in the basic and advanced emergency skills groups. Current certification in BLS, ACLS, PALS and AMLS has a positive impact on registrars‟ self-perceived levels of competence in emergency skills. Registrars who had spent less time between community service and starting their specialist training had higher levels of self-perceived competence in intermediate and advanced emergency skills.
Keywords: Emergency Medical Services; Medical Staff, Hospital